2014
DOI: 10.1021/ac500199x
|View full text |Cite
|
Sign up to set email alerts
|

Detection and Quantification of Early-Stage Malaria Parasites in Laboratory Infected Erythrocytes by Attenuated Total Reflectance Infrared Spectroscopy and Multivariate Analysis

Abstract: New diagnostic modalities for malaria must have high sensitivity and be affordable to the developing world. We report on a method to rapidly detect and quantify different stages of malaria parasites, including ring and gametocyte forms, using attenuated total reflectance Fourier transform infrared spectroscopy (ATR-FT-IR) and partial least-squares regression (PLS). The absolute detection limit was found to be 0.00001% parasitemia (<1 parasite/μL of blood; p < 0.008) for cultured early ri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
111
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 73 publications
(120 citation statements)
references
References 27 publications
8
111
1
Order By: Relevance
“…A number of recent studies have reported on strategies to exploit physical and/or electromagnetic features of hemozoin crystals to detect infection by malaria parasites [54,[80][81][82][83][84][85][86]. Generally, the LOD of these methods is between 1 and 30 iRBCs/ml and, therefore, not as sensitive as NAA strategies.…”
Section: Emerging Malaria Diagnosticsmentioning
confidence: 99%
“…A number of recent studies have reported on strategies to exploit physical and/or electromagnetic features of hemozoin crystals to detect infection by malaria parasites [54,[80][81][82][83][84][85][86]. Generally, the LOD of these methods is between 1 and 30 iRBCs/ml and, therefore, not as sensitive as NAA strategies.…”
Section: Emerging Malaria Diagnosticsmentioning
confidence: 99%
“…The key factor that renders this analytical method a perfect diagnostic tool, in comparison to other molecular methods, is its non‐destructive, cost‐effective and label‐free nature. Over the years, infrared (IR) and Raman spectroscopic techniques have been employed to study a number of different diseases, such as cancer, neurological diseases, prenatal disorders and many others . Within the field of disease investigation, spectroscopy has the potential to diagnose and monitor a disease, while at the same time assessment of surgical margins of a tumour or determination of the subtype of a disease is also feasible.…”
Section: Introductionmentioning
confidence: 99%
“…Fourier transform infrared (FTIR) spectroscopy to study blood‐based samples is not a new concept and there are several reports showing a usefulness of infrared spectroscopy for diagnosis, monitoring progression of diseases and their treatment by investigation of erythrocytes , leukocytes , platelets , plasma , and serum . Instead of the quantification of a single or a few biomarkers, on which most of the blood tests rely, the total biochemical composition of a sample is analyzed in a single and rapid measurement of plasma IR spectrum including peptides, proteins, lipids, RNA and others.…”
Section: Introductionmentioning
confidence: 99%